Aid is dead. Long live aid! - Jean-Michel Severino (Field Actions Science Reports, 2012)
The concepts, targets, tools, institutions and modes of operation of official development assistance have been overtaken by the pace of change in a world marked by the combined momentum of demography, technology and economic growth. Aid can however recover, as social consequences of the globalization call for new forms of regulation. It will then be necessary to modify and diversify our target-setting processes, to update operating procedures, and to find better ways of measuring policy implementation. Aid volumes will certainly continue to grow, and we must transform the way aid is financed. Public and private aid stakeholders must recognize the importance of these transformations and be ready to support them, by questioning the methods as well as the objectives of the policies they are implementing. Otherwise, they will severely impede the emergence of the policies we need if we are to build a better world.